AKAR-AKAR DAKWAH ISLAMIYYAH: (AKIDAH, IBADAH DAN SYARIAH) - A. R Idham Kholid (ORASI: Jurnal Dakwah dan Komunikasi, 2017)
In principle, human beings as one of God's creatures need religion because religion is the basis of rules and guidelines that are needed by humans in life and able to deliver to the happiness in the world and in the hereafter. This fact certainly becomes very important to realize that the human being as a weak servant would require the presence of the Most Powerful God, and to know the Lord takes religion. Therefore, to be a good servant of God must necessarily have a true faith, and to worship in accordance with what has been outlined in the law. By having a true faith, and to practice in accordance with the law, becomes a perfect servant of God who can live life with full of happiness and the right to reply paradise of Allah.